The New Safety Net: Dairy Margin Protection Program Participation and Payouts - R. Reid (Kansas Agricultural Experiment Station Research Reports, 2015)
The Dairy Margin Protection Program created by the 2014 Farm Bill offers a new risk management option available for dairy producers. By “insuring” a margin between the price of milk and the cost of feed inputs, producers can have protection from declining milk prices, rising feed costs, or both. More than half of the dairies in the U.S. participated in at least the catastrophic level of coverage for 2014, which locks them into participating through 2018 when a new Farm Bill is written. Coverage level and production history enrolled can change year to year however; therefore, each year producers will be facing tough risk management decisions. Factors influencing their decision to purchase the “correct” level of coverage include operation size (due to premium structure), market outlook, risk preference, and financial position.
Keywords: MPP-Dairy; risk management; dairy margin